1995
DOI: 10.1093/oxfordjournals.humrep.a136252
|View full text |Cite
|
Sign up to set email alerts
|

Implantation: Two instead of three embryo transfer in in-vitro fertilization

Abstract: The rational of transferring two instead of three embryos was studied through 468 in-vitro fertilization (IVF) treatment cycles in 287 couples. The quality of 1224 embryos was determined according to the fragmentation rate and the morphology as good (A) and poor (B). The influence of the number of embryos transferred (two or three) on the pregnancy rate when the same quality or combinations of good and poor quality embryos transferred was examined. When only good quality embryos were transferred the pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 0 publications
2
25
0
1
Order By: Relevance
“…Several observational studies have reported comparable pregnancy rates, with an accompanying maintenance or reduction in multiples, for DET compared with TET in young women with good prognoses. Although a significant incidence of HOM was reported after TET in all studies (3.9-18.0%), none resulted from DET in these series [85][86][87][88][89].…”
Section: Women Under the Age Of 35 Yearsmentioning
confidence: 92%
“…Several observational studies have reported comparable pregnancy rates, with an accompanying maintenance or reduction in multiples, for DET compared with TET in young women with good prognoses. Although a significant incidence of HOM was reported after TET in all studies (3.9-18.0%), none resulted from DET in these series [85][86][87][88][89].…”
Section: Women Under the Age Of 35 Yearsmentioning
confidence: 92%
“…In 1996, Jurisicova et al (2) found that cellular fragmentation might induce apoptosis of blastomeres. Embryos with extensive fragmentation are known to have lower implantation rates, presumably due to a reduction of cytoplasm available for normal cell division or reduced intercellular communication resulting from obstructed gap junctions (3)(4)(5). In retrospective studies, severe fragmentation has been associated with diminished implantation rates (3)(4)(5).…”
mentioning
confidence: 99%
“…The average number of embryos transferred per IVF cycle ranged from 3.6 to 4.2 [57]; a figure all the more striking given that improved IVF techniques had led researchers to observe that pregnancy rates could be maintained with fewer embryos being transferred [58][59][60][61].…”
Section: Usa: 20 Years Of Embryo Transfer Guidelinesmentioning
confidence: 99%